Neue Ergebnisse aus den Arbeiten an der Transportstraße aus Kalksteinblöcken in Dahschur: Bemerkungen zu dem Dekorationsprogramm des Tempels am Aufweg der Knickpyramide sowie neuen Funden und deren Bedeutung für den Abbau der Monumente im Snofru-Tal - Gospodar, Kyra (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
The extensive necropolis site of Dahshur shows several megastructures, among them the pyramid complexes of the Bent Pyramid and the Black Pyramid. Equally impressive as the size and importance of these megastructures is the effort which was necessary for the maintenance of these buildings and their associated cultic activities. Although these endeavours must have lasted for some time, excavations conducted by the German Archaeological Institute Cairo of a transportation pathway consisting of limestone spolia show that the so-called Valley Temple of the Bent Pyramid and its wider surroundings were systematically deconstructed in the early Ramesside Period. So far, most of the fragments clearly belong to the decoration of the temple of the Bent Pyramid. Some of the decorated fragments display previously unknown scenes which contribute greatly to the understanding of early temple decoration. In 2019, a decorated limestone block displaying names and titles of Amenemhet Ill was found built into the pavement of the pathway. This spectacular find suggests that the deconstruction of building structures in Dahshur was planned on a larger scale and went far beyond the precinct of the Bent Pyramid's Valley Temple.